FEMINIST NARRATIVE AND STYLISTICS ANALYSIS IN THE DETECTIVE GENRE: ENOLA HOLMES 2 - Dalimunte, Sukma Rahayu; Turnip, Novi Kanaya Perdana; Simanjuntak, Jessica Ruth Margaretha; Br Panjaitan, Eureka Jovita; Rangkuti, Rahmadsyah (BASIS (Bahasa dan Sastra Inggris), 2025)
This research described the feminist stylistic and gender specifications in Enola Holmes 2 movie. The method used in this research is a qualitative method and the theory applied is feminist stylistics theory by Sarah Mills. The researchers analysed the collected data based on the level of words, phrases or sentences, and discourses. The objectives of this research are some words, sentences and discourses in the Enola Holmes 2 Movie’s Script that refers to the feminist stylistics, such as the diction, language used, figurative language and how the style affects the feminist value in Enola Holmes 2 movie. The result found in this research is the different styles in presenting female and male by the script writer. Females are represented with feminine words and mostly represented by their physical appearances, feminine stereotypes, and beauty behaviours. Meanwhile, males are represented with masculine words and mostly represented by their strong characteristics. Also, masculine stereotypes and many occupation titles or jobs refer to men rather than women. It proved that the script writer shows men involved more in the professional world than women, especially in investigating professions like detective.